Taxation methods as a solution of social problems in Latvia - Andreeva, Tatyana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article is devoted to the study of the problems of state regulations in the field of taxation. The purpose of this article is to analyse distributing and stimulating functions of taxes taking into account the actual situation in the discussed field. The article analyzes such issues as the increase of contributions in social insurance, changes in personal income tax, the use of stimulation function of value added tax. Special attention is paid to the introduction of differentiated non-taxable allowance and tax of solidarity in Latvia. A differential personal allowance means that not all taxpayers will have the same level of personal allowance, as its level will be set according to the taxpayer’s level of income. The purpose of the introduction of solidarity tax is to reduce the regressivity of the taxation for the recipients of high levels income
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 465, s. 9-20
Keywords: taxes; tax system; social insurance contributions; personal income tax; value added tax; differentiated non-taxable allowance; solidarity tax; podatki; system podatkowy; udział zabezpieczenia społecznego; podatek od dochodów osobistych; PIT; podatek od wartości dodanej; VAT; zróżnicowane zwolnienia podatkowe; podatek solidarnościowy